Efficacy and toxicity of molecular targeted therapies in combination with docetaxel for metastatic castration-resistant prostate cancer: a meta-analysis of phase III randomized controlled trials. (June 2015) - Qi, Wei-Xiang; Fu, Shen; Zhang, Qing; Guo, Xiao-Mao
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose: For patients with metastatic castration-resistant prostate cancer (CRPC), the efficacy and safety of molecular targeted agents (MTAs) in combination with docetaxel are still unclear. We conducted this meta-analysis to assess the efficacy and toxicity of the addition of MTAs to docetaxel-based chemotherapy for the treatment of metastatic CRPC. Methods: Databases from PubMed, Web of Science, and abstracts presented at American Society of Clinical Oncology meeting up to 31 June 2014 were searched to identify relevant studies. Eligible studies included prospective phase III randomized controlled trials (RCTs) evaluating docetaxel with or without MTAs in patients with metastatic CRPC. The primary aim was to assess overall survival (OS). Secondary aims were to assess progression-free survival (PFS); overall response rates (ORRs), and grade 3–5 toxicities. Statistical analyses were conducted by using either random effects or fixed-effect models according to the heterogeneity of included studies. Results: A total of 5886 patients from five phase III RCTs were identified. No statistically significant difference in OS [hazard ratio (HR): 0·98, 95% confidence interval (CI): 0·91–1·04, P = 0·44], ORR [relative risk (RR): 1·32, 95% CI: 0·94–1·84, P = 0·11], and PSA response rate (RR: 1·22, 95% CI: 0·86–1·74, P = 0·27) was found between the two groups. The addition of MTAs to docetaxel significantly improved PFS (HR: 0·92, 95% CI: 0·86–0·98, P = 0·011). However, the benefits in PFS was accompanied by increasing the risk of developing grade 3–4 (RR: 1·19, 95% CI: 0·99–1·42, P = 0·062) and fatal (RR: 1·30, 95% CI: 1·01–1·66, P = 0·039) adverse events. Conclusions: The findings of this study suggest that the palliation of CRPC with MTAs and docetaxel does not provide a significant survival benefit and is associated with increased severe toxicities.